Facts and their interpretation in the text of the medieval travelogue (Eurasian Journal of Philology Science and Education, 2018)
The proposed publication is devoted to one of the problems of medieval studies – the genre peculiarity of «The Journey of the Three Seas» by Afanasy Nikitin. With the development of research of travel notes in science new definitions are being introduced that allow us to concretize the genre parameters of the most interesting facts of the literary experience of travel narratives and impressions of them. In this case we are talking about the trawelogue. The essence and evolution of the genre is indicative also in the field of Old Russian literature, the property of which is the contribution of the Russian merchant Afanasy Nikitin, who made a long journey through the countries of the East and left written testimonies about the knowledge of the world, a unique culture and himself on the way to God.